Perspective on carbazole-based organic compounds as emitters and hosts in TADF applications. Issue 34 (21st August 2017) - Wex, Brigitte; Kaafarani, Bilal R.
Abstract : Perspective covering carbazole-containing emitters and hosts for third generation TADF (thermally-activated delayed fluorescence) OLED technology along with computational benchmark studies. Abstract : The field of organic light-emitting devices (OLEDs) has undergone a remarkable journey since its discovery by Tang and VanSlyke with an alternation of utilizing fluorescence and phosphorescence as the emitting vehicle. The latest generation of thermally activated delayed fluorescence (TADF) materials harvest triplet excited states back into the singlet manifold. This booming field has yielded a large array of new compounds as both emitters and hosts. This review is limited to TADF emitters utilizing at least one carbazole unit as a donor and organized according to the various acceptor building blocks such as cyanophenyl, pyridine, biphenyls, anthraquinone, phenyl(pyridine-2-yl)methanone, benzophenone, xanthon, sulfones, triazines, benzils, dicyanopyrazines, diazatriphenylene, and others. A survey of carbazole-containing host materials follows. Density functional theory (DFT) has carved out a significant role in allowing the theoretical prediction of ground state properties for materials applied in OLED technology. Time-dependent DFT extends the reach to model excited state properties important to rationalize the light-output in OLED technology. For TADF, two fundamental factors are of interest: significant separation of frontier molecular orbitals and minimal singlet–triplet energy gap (Δ E ST ). In this review, the utilization of DFT calculations to optimize geometries for the visualization of frontier molecular orbital separation was surveyed to find that the B3LYP/6-31G(d) level of theory is the overwhelmingly used approach. In addition, we review the more in-depth approaches to utilizing DFT and time-dependent DFT (TD-DFT) with optimized percentage Hartree–Fock (OHF) and long-range corrected hybrid functionals, tuning procedures and others in an attempt to best quantify the size of Δ E ST as well as the nature of the triplet state as locally excited state (LE) and charge-transfer state (CT).